Pengaruh Fitur, Layanan Pelengkap dan Garansi Terhadap Keputusan Pembelian Handphone (Studi Kasus Pada Mahasiswa S1 Fakultas Ekonomi dan Bisnis Universitas Udayana Denpasar) - Putra, Putu Agus Wira; Seminari, Ni Ketut (E-Jurnal Manajemen, 2014)
Mobile is a communication tool that has a very good role that causes the mobile phone users in Indonesia, especially college students is increasing every year. The variables studied were the features, complementary services and warranty on purchase decision. Based on accidental sampling technique, the number of samples in this study were 180 respondents. The results of multiple linear regression analysis showed that the features, complementary services and warranty simultaneously positive and significant impact on mobile phone purchasing decision on colleger in Faculty of Economics and Business Udayana University. Feature, service and warranty partially complementary positive and significant impact on mobile phone purchasing decision on colleger in Faculty of Economics and Business Udayana University.
Keywords: features; complementary services; warranty; purchasing decisions